Development of a Water Allocation Model for Equitable Water Distribution at Doho Rice Irrigation Scheme, Uganda - Bwambale, Erion; Gathogo Home, Patrick; Messo Raude, James; Wanyama, Joshua (Hydrology, 2019)
The shortage of irrigation water at the tail reaches of Doho Rice Irrigation Scheme especially in the dry season has resulted in decreased rice production. At Doho Rice Irrigation Scheme, water distribution follows a predetermined rotation system where allocated supplies are unknown and the farmer decides how much water they divert to their plot. This has resulted in water inequalities between the tail end and head end blocks of the scheme. The main objective of the study was to develop a water allocation model for equitable distribution of irrigation water taking into account crop growth stages. This study developed an equitable water allocation model by ensuring that the crop water requirements per block are matched with the available supply in the main canal. A water delivery scheduling model was developed to help deliver the decadal irrigation water requirements by grouping different blocks together. The water allocation model gives required irrigation supplies and recommended supplies depending on the crop growth stage and acreage per block. The results from the water delivery scheduling model suggest a 2 days of irrigation per week for the land preparation, development and late seasons and 3 days of irrigation per decade during the high consumptive stages of initial and midseason stages of rice development.
Keywords: Equitable; Irrigation; Model; Schedule; Seepage